Taking Turns or Not? Children's Approach to Limited Resource Problems in Three Different Cultures. Issue 3 (May 2016) - Zeidler, Henriette; Herrmann, Esther; B. M. Haun, Daniel; Tomasello, Michael
Abstract : Some problems of resource distribution can be solved on equal terms only by taking turns. We presented such a problem to 168 pairs of 5‐ to 10‐year‐old children from one Western and two non‐Western societies (German, Samburu, Kikuyu). Almost all German pairs solved the problem by taking turns immediately, resulting in an equal distribution of resources throughout the game. In the other groups, one child usually monopolized the resource in Trial 1 and sometimes let the partner monopolize it in Trial 2, resulting in an equal distribution in only half the dyads. These results suggest that turn‐taking is not a natural strategy uniformly across human cultures, but rather that different cultures use it to different degrees and in different contexts.